Palimpsests : poems based on the classics that speak to the present - Mann, Chris, 1948- (Book collections on Project MUSE., 2021)
"Like a modern Orpheus, Chris Mann explores the underworld of the past and returns with peculiarly African poetry, based on the classics that deepens our understanding of the present. In this collection, youthful Narcissus gazes into a mobile phone, wandering Odysseus sails the seas of the Internet, and picknickers beside a river's pool in South Africa encounter the shades. The satirical poets of ancient Rome mock a strangely familiar hunger for sex and power among politicians, dispossessed Britons revolt against the empire, Vandals ruthlessly plunder wealth and land, and tech-savvy Phoenicians colonise the coast of a pastoral Africa. Rising seas engulf the lost city of Atlantis, and a terrible plague devastates the Athens of Socrates, Pericles, and the Parthenon. Palimpsests speaks to the interplay of different cultures and how the past is interwoven in the fabric of the present. It is a fresh, new offering enabling lovers of the classics to experience this world in a unique, modern and African way."--